Perception of Faculty Regarding Competency-based Medical Education - Amita Aditya (Journal of Clinical and Diagnostic Research, 2024)
Dear Editor, This is in relation to the article titled “Perception of Faculty regarding Competency-based Medical Education (CBME): A Qualitative Study from Mizoram, India.” [1] Authors have touched upon a very relevant topic as it is the need of the hour to increase the awareness regarding competency-based system amongst the healthcare professionals. Competency is defined as “the ability to do something successfully and efficiently,” [2] and CBME is an approach to guarantee that the graduates develop the competencies necessary to meet the needs of the patients in the community [3]. Being learner-centric, it de-emphasises timebased training and ensures better flexibility and accountability.